Identification of CMY-2-type cephalosporinases in clinical isolates of Enterobacteriaceae by MALDI-TOF MS - Papagiannitsis, C C; Kotsakis, S D; Tuma, Z; Gniadkowski, M; Miriagou, V; Hrabak, J (Antimicrobial agents and chemotherapy, 2014)
This study exploited the possibility to detect Citrobacter freundii-derived CMY-2-like cephalosporinases in Enterobacteriaceae clinical isolates using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Periplasmic proteins were prepared using a modified sucrose method and analyzed by MALDI-TOF MS. A ca. 39,850-m/z peak, confirmed to represent a C. freundii-like β-lactamase by in-gel tryptic digestion followed by MALDI-TOF/TOF MS, was observed only in CMY-producing isolates. We have also shown the potential of the assay to detect ACC- and DHA-like AmpC-type β-lactamases.
Keywords: bakteriální proteiny; Bacterial Proteins; Cephalosporinase; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Enterobacteriaceae; cefalosporinasa